2020
DOI: 10.3390/v12070735
|View full text |Cite
|
Sign up to set email alerts
|

Heat Inactivation of Different Types of SARS-CoV-2 Samples: What Protocols for Biosafety, Molecular Detection and Serological Diagnostics?

Abstract: Standard precautions to minimize the risk of SARS-CoV-2 transmission implies that infected cell cultures and clinical specimens may undergo some sort of inactivation to reduce or abolish infectivity. We evaluated three heat inactivation protocols (56 °C-30 min, 60 °C-60 min and 92 °C-15 min) on SARS-CoV-2 using (i) infected cell culture supernatant, (ii) virus-spiked human sera (iii) and nasopharyngeal samples according to the recommendations of the European norm NF EN 14476-A2. Regardless of the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
149
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(163 citation statements)
references
References 21 publications
11
149
0
1
Order By: Relevance
“…For SARS-CoV-2, after 30 min at 56 °C, the magnitude of the virus titre reduction was 3.0 log 10 [ 33 ], ≥4.6 log 10 [ 37 ], ≥5.0 log 10 [ 66 ], ≥5.9 log 10 [ 67 ], 5.0–6.0 log 10 [ 69 ], and 7.0 log 10 [ 70 ]. At 60 °C, there was a 7.0 log 10 reduction after 15 min [ 70 ], and a 5.0–6.0 log 10 reduction (complete inactivation) in clinical samples after 60 min [ 69 ] ( Table 5 ). According to an unpublished study [ 67 ], at 65 °C, SARS-CoV-2 was inactivated (≥5.5 log 10 reduction) in cell culture, nasopharyngeal samples, and serum after 15, 10, and 10 min, respectively ( Table 5 ).…”
Section: Disinfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For SARS-CoV-2, after 30 min at 56 °C, the magnitude of the virus titre reduction was 3.0 log 10 [ 33 ], ≥4.6 log 10 [ 37 ], ≥5.0 log 10 [ 66 ], ≥5.9 log 10 [ 67 ], 5.0–6.0 log 10 [ 69 ], and 7.0 log 10 [ 70 ]. At 60 °C, there was a 7.0 log 10 reduction after 15 min [ 70 ], and a 5.0–6.0 log 10 reduction (complete inactivation) in clinical samples after 60 min [ 69 ] ( Table 5 ). According to an unpublished study [ 67 ], at 65 °C, SARS-CoV-2 was inactivated (≥5.5 log 10 reduction) in cell culture, nasopharyngeal samples, and serum after 15, 10, and 10 min, respectively ( Table 5 ).…”
Section: Disinfectionmentioning
confidence: 99%
“…According to an unpublished study [ 67 ], at 65 °C, SARS-CoV-2 was inactivated (≥5.5 log 10 reduction) in cell culture, nasopharyngeal samples, and serum after 15, 10, and 10 min, respectively ( Table 5 ). The efficacy of heat treatment against SARS-CoV-2 was also evaluated at other temperatures that varied among studies, including 70 °C [ 37 , 39 , 68 ], 92 °C [ 69 ], 95 °C [ 67 ], and 98 °C [ 66 ] ( Table 5 ).…”
Section: Disinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the precise composition of many commercial reagents is proprietary, preventing ingredient-based inference of inactivation efficacy between reagents. Some limited preliminary data on SARS-CoV-2 inactivation by heat (14,15) or chemical (16)(17)(18)(19)(20)(21) Vero E6 cells at a multiplicity of infection (MOI) of 0.001, in the presence of 5% FCS. Cell culture supernatants were collected 72 hours post infection, clarified for 10 mins at 3000 × g, aliquoted and stored at -80°C until required.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Heating influenza virus at 60 °C for 15 min at 25% relative humidity (RH) resulted in a decrease of 1 log 10 -fold in viral titers, whereas the same heating process at 50% RH reduced viral titers by a factor of 4 log 10 -fold. 24 Although SARS-CoV-2 has been shown to be efficiently inactivated by heat in solution, 25 a comparison of inactivation by dry or moist heat when the virus is dried on surfaces has not been carried out, although one study found that stability of SARS-CoV-2 is lower in high humidity at common environmental temperatures (≤38 °C). 26 …”
mentioning
confidence: 99%